Dedifferentiated retroperitoneal large liposarcoma and laparoscopic treatment: Is it possible and safe? The first literature case report. (2019) - Agrusa, Antonino; Di Buono, Giuseppe; Buscemi, Salvatore; Randisi, Brenda; Gulotta, Leonardo; Sorce, Vincenzo; Badalamenti, Giuseppe; Albano, Domenico; Galia, Massimo; Romano, Giorgio; Gulotta, Gaspare
Highlights: We describe a case report of large retroperitoneal dedifferentiated liposarcoma totally treated by laparoscopic surgery. In literature we found few cases of laparoscopic treatment only for Well-Differentiated liposarcoma. To our knowledge this is the first description of Dedifferentiated liposarcoma completely treated with laparoscopic technique. Literature review was performed to identify outcomes and advantages of laparoscopic approach for. Abstract: Introduction: Soft tissue sarcomas are rare neoplasms often characterized by local invasiveness and distant metastasis with poor prognosis for affected patients. Among the most frequent sarcomas we find well-differentiated and dedifferentiated liposarcomas characterized by a better survival compared to the other histological types. When it is possible the only curative treatment for these neoplasms is surgical resection. Case report: We report a case of a 62-year-old caucasian woman with CT abdominal scan that demonstrated a voluminous solid oval mass in the left perirenal space with dislocation of the kidney and in continuity with the anterior renal fascia. After a percutaneous CT-guided biopsy of the mass the histopathological diagnosis was a dedifferentiated retroperitoneal liposarcoma. We performed a laparoscopic surgical resection of the retroperitoneal mass in block with kidney and left adrenal gland. Discussion: When possible, surgical resection with adequate margins represents the only curative therapeutic option for this pathology. Only a few papers are available in literature which take into consideration the possibility of laparoscopic approach for retroperitoneal masses with better vision of surgical field, reduction of post-operative pain and better cosmesis. Conclusion: A retroperitoneal mass represents a serious diagnostic challenge. The choice of the best surgical procedure can benefit to the patient prognosis. To our opinion laparoscopy can be a safe and successful treatment and it can represent a valid alternative to open surgery. However, we have no randomized controlled trials that compare laparoscopic versus open resection for retroperitoneal liposarcomas.